Aerobic Exercise Training and Nontraditional Cardiovascular Risk Factors in Hemodialysis Patients: Results from a Prospective Randomized Trial - Oliveira E Silva, Viviana Rugolo [UNESP]; Stringuetta Belik, Fernanda [UNESP]; Hueb, João Carlos [UNESP]; De Souza Gonçalves, Renato [UNESP]; Costa Teixeira Caramori, Jacqueline [UNESP]; Perez Vogt, Bárbara [UNESP]; Barretti, Pasqual [UNESP]; Zanati Bazan, Silméia Garcia [UNESP]; De Stefano, Greicy Mara Mengue Feniman [UNESP]; Martin, Luis Cuadrado [UNESP]; Da Silva Franco, Roberto Jorge [UNESP] (Karger Publishers, 2019)
Introduction: Chronic kidney disease (CKD) patients have a high incidence of cardiovascular diseases (CVD) which increases their morbidity and mortality. A sedentary lifestyle in CKD is directly linked to the onset of CVD. Physical activity can bring beneficial effects to CKD patients. Aims: The aim of this study was assess the impact of aerobic training on nontraditional cardiovascular risk factors in CKD patients on hemodialysis. Materials and Methods: This is a prospective, controlled, and randomized clinical trial with analysis of intention to treat. Thirty patients underwent an exercise treadmill test, an arterial stiffness evaluation, echocardiography and analysis of endothelial reactivity, and carotid ultrasound and laboratorial tests, including analysis of serum aldosterone. The intervention group (IG) (n =15) underwent aerobic exercise during hemodialysis 3 times a week for 4 months. The control group (CG) (n =15) had no intervention. All of the patients were reassessed after 4 months. Results: In the IG, there was a statistically significant improvement in flow-mediated vasodilation (FMV; p = 0.002) and a reduction in left ventricular hypertrophy (p = 0.006) and serum aldosterone (p = 0.016). There was an increase in C-reactive protein in the CG (p = 0.002). Conclusion: This aerobic training protocol was able to improve endothelial function with enhanced FMV and reduce left ventricular hypertrophy and serum aldosterone, which could have a positive impact on the reduction of nontraditional cardiovascular risk factors in CKD patients on hemodialysis.
Keywords: Cardiovascular diseases; Chronic kidney disease; Left ventricular hypertrophy; Physical activity